2017
DOI: 10.3390/chemosensors5030022
|View full text |Cite
|
Sign up to set email alerts
|

vQRS Based on Hybrids of CNT with PMMA-POSS and PS-POSS Copolymers to Reach the Sub-PPM Detection of Ammonia and Formaldehyde at Room Temperature Despite Moisture

Abstract: Nanocomposite-based quantum resistive vapour sensors (vQRS) have been developed from the assembly of hybrid copolymers of polyhedral oligomeric silsesquioxane (POSS) and poly(methyl methacrylate) (PMMA) or poly(styrene) (PS) with carbon nanotubes (CNT). The originality of the resulting conducting architecture is expected to be responsible for the ability of the transducer to detect sub-ppm concentrations of ammonia and formaldehyde at room temperature despite the presence of humidity. In particular, the boosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The calibration of analytes' concentrations lasting one day per volatile organic compound, only eight biomarkers were tested at two concentrations at 1000 and 400 ppb. In this range the evolution of the amplitude of the chemo-resistive response Ar is assumed to be linear with the amount of analyte molecules when Langmuir adsorption is concerned, as already established in previous works [26,66,67]. Then, at higher contents, over several ppm, another linear range corresponding to Henry diffusion will be found and finally, over thousands of ppm, (more than 50% of saturation) clustering will take place.…”
Section: Dynamic Vapour Sensingmentioning
confidence: 85%
See 1 more Smart Citation
“…The calibration of analytes' concentrations lasting one day per volatile organic compound, only eight biomarkers were tested at two concentrations at 1000 and 400 ppb. In this range the evolution of the amplitude of the chemo-resistive response Ar is assumed to be linear with the amount of analyte molecules when Langmuir adsorption is concerned, as already established in previous works [26,66,67]. Then, at higher contents, over several ppm, another linear range corresponding to Henry diffusion will be found and finally, over thousands of ppm, (more than 50% of saturation) clustering will take place.…”
Section: Dynamic Vapour Sensingmentioning
confidence: 85%
“…The promise of "volatolomics" [1,2] is to detect at their very early stages of development different types of cancer [3][4][5][6][7][8][9], tuberculosis [10,11] liver failure [12], kidney failure [13], Parkinson's disease [14], and many others [15][16][17][18][19]. The spheres of application of VOC sensing beyond medicine are food degradation monitoring [20][21][22], environment monitoring, i.e., the indication of hazardous chemical leakage, the monitoring of organic solvent vapour concentration in the air [23][24][25][26], space exploration, and homeland security [27][28][29][30], process control of chemical and food production [31], the monitoring of quality and alcohol content in automotive fuel [32,33] and others [34]. Nanomaterials belonging to fullerene family are already proved to act as a well-recognized component for elaboration of VOC sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth contribution is presented by Sachan et al [22], studying nanocomposite-based quantum resistive vapour sensors (vQRS), developed from the assembly of hybrid copolymers of polyhedral oligomeric silsesquioxane (POSS) and poly(methyl methacrylate) (PMMA) or poly(styrene) (PS) with carbon nanotubes (CNT). These novels transducers are employed to detect sub-ppm concentrations of ammonia and formaldehyde at room temperature despite the presence of humidity.…”
Section: The Special Issuementioning
confidence: 99%
“…Formaldehyde is a highly toxic substance and widely used in indoor decoration, coating, textile industry, and other fields. The World Health Organization’s International Agency for Research on Cancer identified formaldehyde as a Class 1 carcinogen as early as 2004. Formaldehyde is not only recognized as an allergen and a potentially potent mutagenic substance, which can stimulate human skin, mucous membrane, and respiratory system, but also a direct cause of leukemia. , Pregnant women in the formaldehyde environment for a long time will cause fetal abnormalities. , Its damage to human health can never be ignored, known as a “health killer”. Furthermore, formaldehyde hidden in wardrobe, wallpaper, wall paint, and other home decoration materials can volatilize outward for 3–15 years. , Formaldehyde pollution remains a long-lasting global challenge . Hence, it is urgent to develop an effective and recyclable formaldehyde removal method to improve the quality of human life.…”
Section: Introductionmentioning
confidence: 99%